(untitled) (MAUSAM, 1983)
Satellite meteorological informations in recent years have proved to be a unique tool in aeronautical operations. Although about 12000 stations throughout the world are taking surface synoptic observations several times a day and about 1200 stations upper wind and radiosonde observations twice daily to provide meteorological informations for aeronautical operations, still there are vast data sparse regions over the globe such as big deserts, Inaccessible mountain ranges and oceanic areas. With the launch of first U.S. weather satellite TIROS-l in April 1960, it was possible for the first time to get up-to-date information over the entire globe through visible and infrared imagery. The better quality pictures from polar orbiting satellites received in both visible and infrared channels have been very helpful to an aviation forecaster In recent years over Indian sub-continent. In the present paper, various cloud characteristics associated with potentially hazardous weather phenomena for aviation such as tropical cyclones, jet-streams, squall lines, tornadoes, fogs etc have been discussed with the special emphasis on the safety of the aircraft.